222k views
0 votes
Any volunteer please help

Any volunteer please help-example-1
Any volunteer please help-example-1
Any volunteer please help-example-2
User Suhprano
by
6.0k points

1 Answer

2 votes

Answer:

Part A)

The equation in the point-slope form is:


y-11=(4)/(3)\left(x-\left(-2\right)\right)

Part B)

The graph of the equation is attached below.

Explanation:

Part A)

Given

  • The point = (-2, 11)
  • m = 4/3

The point-slope form of the line equation is


y-y_1=m\left(x-x_1\right)

Here, m is the slope and (x₁, y₁) is the point

substituting the values m = 4/3 and the point (-2, 11) in the point-slope form of the line equation


y-y_1=m\left(x-x_1\right)


y-11=(4)/(3)\left(x-\left(-2\right)\right)

Thus, the equation in the point-slope form is:


y-11=(4)/(3)\left(x-\left(-2\right)\right)

Part B)

As we have determined the point-slope form which passes through the point (-2, 11) and has a slope m = 4/3

The graph of the equation is attached below.

Any volunteer please help-example-1
User Danmoreng
by
6.3k points